The Integrative Approach in the Process of Studying Conducting - Marnauza, Māra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
Many-sided activity of a conductor requires not only wide knowledge and skills in different areas of music, but also knowledge in interaction and management, verbal and non-verbal communication skills, skills in choir management, that determines the necessity to use an integrative approach in the study process of conducting. The aim of the study is to research the peculiarities of integrated approach used in study process of conducting, to work out the criteria for evaluation of conductor’s professional readiness and the ideal model of conductor. The methods used in the study are the analisis of literature, modelling, questionnaire and acquirement. The purposfullness in the choice of study content is promoted by criteria of conductors professional readiness: the self-acknowledgment for a conductor as a musician, communicative skills for conductor as a personality in interaction, self-management for a conductor as a choir manager.